Chemo- and Regioselective Syntheses of Enantiopure Aminopyrrolidinones as Building Blocks for Constrained Peptidomimetics - Waibel, Reiner; Gmeiner, Peter; et al. (Heterocycles, 1999)
Starting from natural asparagine the synthesis of the N-protected enantiomerically pure 3- and 4-aminopyrrolidinones (1) and (3) was accomplished. The incorporation of these building blocks into conformationally constrained peptidomimetics was demonstrated by the synthesis of the potential dopamine receptor modulator (14b) (β-PAOPA). Furthermore, Freidinger γ-lactams including the protected dipeptide mimetics (8a-c) and (9) were prepared. The optical integrity of the synthesis was established by NMR analysis of the ureas (10a,b).
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.lphch.chemoa